Analisis Perawatan Berkala Trafo Distribusi 800 kVA pada Rumah Sakit X Kota Tangerang - Kusuma, Ridho Alpha; Prayogo, Jimmy Arimas; Mufit, Choirul (Universitas Semarang, 2023)
In Indonesia, electricity supply for buildings or buildings with needs above 200kVA requires a distribution transformer owned by the customer, so that electrical energy transactions are carried out on the medium voltage side of 20kV. The distribution transformer in a hospital is a very vital component, especially during the COVID-19 pandemic where transformers are forced to continue operating above nominal levels without any maintenance. Distribution transformer maintenance includes visual inspection, monthly maintenance, maintenance every six months and annual maintenance. Treatments carried out on distribution transformers at X Hospital are DGA (Dissolved Gasses Analysis), transformer insulation testing, TTR (Transformer Turn Ratio) testing, Breakdown Voltage testing, thermovision testing and Winding Resistance testing; In addition, treatment or purification of transformer oil is also carried out based on testing. all dissolved gas and total dissolved gas (TDCG) decreased after the purification process and after purification there is still residual dissolved gas in the transformer. Interpretation of dissolved gas data (DGA) using several methods indicates a